Workplace harassment and burnout syndrome among health personnel at a referral hospital - Marín Marín, Diego (2023)
Objective: To determine the association between workplace harassment and burnout syndrome among healthcare personnel of a Peruvian referral hospital. Materials and methods: An analytical cross-sectional study which included internists, surgeons, nurses, residents, internsand nursing technicians from the Medicine and Surgery departments of Hospital Nacional Hipólito Unanue in Lima, Peru. The Maslach Burnout Inventory–Human Services Survey (MBI–HSS) and the Negative Acts Questionnaire–Revised (NAQ–R)were used for the assessment of burnout and harassment, respectively. Additionally, the association with age, gender, occupation, marital status, workplace, salary satisfaction, family burden, physical activity, harmful habits, vacations, religious affiliation, number of jobs, monthly remuneration, job tenure, working hours per week, number of patients seen per day, weekly shifts and rest hours was evaluated. A multivariate analysis was conducted using a multiple logistic regression model and the presence or absence of burnout as an outcome variable. Results: The study consisted of 206 participants, out of whom 22 (10.7 %) suffered burnout and 27 (14 %) moderate tosevere harassment. In the bivariate analysis, age (OR 0.94; 95 % CI 0.89–0.99; p = 0.02), marital status such as married and cohabiting (OR 2.85; 95 % CI 1.01–8.06; p = 0.04) and harassment (OR 5.20; 95 % CI 1.92–14.09; p = 0.009) were associatedwith burnout. In the multivariate analysis, the only significant predictor of burnout was workplace harassment. Moderate to severe harassment was associated with OR 4.00 (95 % CI 1.4–11.3; p = 0.009) compared to mild harassment. Conclusions: It is important to identify health workers suffering workplace harassment due to its strong associationwith burnout syndrome. It is essential to carry out further research to understand and address the problem of workplace harassment and its influence on the development of burnout, as well as studies to evaluate interventions aimed at preventing both workplace harassment and burnout.